Adolescent cannabis and tobacco use and educational outcomes at age 16: birth cohort study. - Stiby, Alexander I.; Hickman, Matthew; Munafò, Marcus R.; Heron, Jon; Yip, Vikki L.; Macleod, John (Addiction, 2015)
Aims To investigate the relationship between cannabis and tobacco use by age 15 and subsequent educational outcomes. Design Birth cohort study. Setting England. Participants The sample was drawn from the Avon Longitudinal Study of Parents and Children; a core sample of 1155 individuals had complete information on all the variables. Measurements The main exposures were cannabis and tobacco use at age 15 assessed in clinic by computer-assisted questionnaire and serum cotinine. The main outcomes were performance in standardized assessments at 16 [Key Stage 4, General Certificate of Secondary Education (GCSE)] in English and mathematics (mean scores), completion of five or more assessments at grade C level or higher and leaving school having achieved no qualifications. Analyses were sequentially adjusted for multiple covariates using a hierarchical approach. Covariates considered were: maternal substance use (ever tobacco or cannabis use, alcohol use above recommended limits); life course socio-economic position (family occupational class, maternal education, family income); child sex; month and year of birth; child educational attainment prior to age 11 (Key Stage 2); child substance use (tobacco, alcohol and cannabis) prior to age 15 and child conduct disorder. Findings In fully adjusted models both cannabis and tobacco use at age 15 were associated with subsequent adverse educational outcomes. In general, the dose-response effect seen was consistent across all educational outcomes assessed. Weekly cannabis use was associated negatively with English GCSE results [grade point difference (GPD), -5.93, 95% confidence interval (CI) = -8.34, -3.53] and with mathematics GCSE results (GPD, -6.91, 95% CI = -9.92, -3.89). Daily tobacco smoking was associated negatively with English GCSE (GPD, -11.90, 95% CI = -13.47, -10.33) and with mathematics GCSE (GPD, -16.72, 95% CI = -18.57, -14.86). The greatest attenuation of these effects was seen on adjustment for other substance use and conduct disorder. Following adjustment, tobacco appeared to have a consistently stronger effect than cannabis. Conclusions Both cannabis and tobacco use in adolescence are associated strongly with subsequent adverse educational outcomes. Given the non-specific patterns of association seen and the attenuation of estimates on adjustment, it is possible that these effects arise through non-causal mechanisms, although a causal explanation cannot be discounted. © 2015 Society for the Study of Addiction